2018
DOI: 10.1029/2018jc014053
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Interannual Variation of Summer Mean Alongshore Current Near the East Coast of Korea Derived From 16‐Year‐Long Observational Data

Abstract: Interannual variation in the summer surface current near the east coast of Korea was analyzed using long‐term (~16 years) time series measurements. Significant interannual variations in the summer alongshore current, which have a magnitude comparable to that of the climatological summer mean (equatorward) current, were observed. Positive anomalies (more poleward) occurred during 2001, 2009, 2010, and 2014; negative anomalies (more equatorward) occurred during 2002, 2006, and 2012. A linear combination of equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Consequently, a thermal front is formed between these cold and warm anomalies. Furthermore, as reported in previous studies (e.g., [59][60][61]), the anticyclonic flows accompanied by northward coastal current reversal are generated by a negative wind stress curl. It may bring relatively warm and fresh water from the southern area into the downwelling region.…”
Section: Occurrence Of Mesoscale Features In the Nessupporting
confidence: 74%
“…Consequently, a thermal front is formed between these cold and warm anomalies. Furthermore, as reported in previous studies (e.g., [59][60][61]), the anticyclonic flows accompanied by northward coastal current reversal are generated by a negative wind stress curl. It may bring relatively warm and fresh water from the southern area into the downwelling region.…”
Section: Occurrence Of Mesoscale Features In the Nessupporting
confidence: 74%
“…Standard error of the mean is employed in the present study for examining the significance of the mean value over the duration of available data, which is different from zero. The standard error of the mean, as in Park and Nam (2018), was calculated by, σstdbold-italicNeff where bold-italicσbold-italicstd is the standard deviation (STD) of the variables and bold-italicNeff can be defined as, bold-italicNeff=Thenumberofdatadoubledefoldingtimelagoftheautocorrelation …”
Section: Methodsmentioning
confidence: 99%
“…Standard error of the mean is employed in the present study for examining the significance of the mean value over the duration of available data, which is different from zero. The standard error of the mean, as in Park and Nam (2018), was calculated by,…”
Section: Estimating the Standard Error Of The Meanmentioning
confidence: 99%
“…The seasonal standard deviations (m s −1 ) for the C of OPS are denoted with italic letters below the C of each segment. Park and Nam, 2018). This boundary condition is justified as the wind stresses at up-shelf grids around the origin was not large compared to those at down-shelf grids (e.g., W9, W18, and W32) so that inclusion of wind stresses at the up-shelf grids does not change the results significantly.…”
Section: Wind-forced Ctw Model and Its Applicationmentioning
confidence: 99%
“…Despite some previous studies explaining the subtidal coastal sea level fluctuations around the KP based on the classical CTW model under varying conditions of stratification and shelf topography (Lee and Chung, 1982;Lyu et al, 2002;Cho et al, 2014), the reasons for the significant difference between the observed (6.1-15.6 m s −1 ) and modeled (4.6-10.3 m s −1 ) propagation speeds are still poorly understood (Cho et al, 2014). In contrast, the subtidal sea level fluctuations off the east coast of the KP are also related to non-isostatic sea level responses to atmospheric pressure disturbances over a period of 2-20 days (Lyu et al, 2002;Nam et al, 2004;Jung et al, 2008), as well as a local upwelling/downwelling response to alongshore wind forcing beyond CTW dynamics (Park and Nam, 2018). Thus, our understanding of subtidal sea level fluctuations around the KP is far from complete; for example, how well the subtidal sea level fluctuations can be explained using the classic CTW and other dynamics beyond CTWs are poorly understood.…”
Section: Introductionmentioning
confidence: 99%